Study of Diameter, Depth and Variation of Relative Flux Density of Moon’s Craters - Upadhayay, D.R.; Khanal, A.; Shahi, S.R. (Scientific World, 2020)
In this work, we have selected three craters Mutus, Mutus C and Nearch of the satellite Moon. The fits images were taken from Meade 16- inch LX200GPS Schmidt- Cassegrain Telescope on June 20, 2018 from National observatory located at Nagarkot, Nepal. To find the diameter, number of lines were drawn across the craters and distance of them were determined in pixel size from Aladin V 2.5 software. By using shadow length method, the height of two craters (Mutus and Nearch) were determined and compared with the published one. In addition to this, variations of relative flux density, Gaussian trend distribution of flux were studied.